Legal Analysis of Sanctions Imposed on Perpetrators of Criminal Acts of Broadcasting False News in Accordance With the Provisions of Articles 27 and 28 of The Ite Law - Myranika Annie; Saurav Kumar (The International Journal of Law Review and State Administration, 2025)
This study examines the legal basis, implementation, and effectiveness of sanctions imposed on perpetrators of criminal acts related to the dissemination of false news as stipulated in Articles 27 and 28 of the Electronic Information and Transactions (ITE) Law. The research aims to analyze the extent to which these provisions provide legal certainty, deterrent effects, and protection for the public against misinformation in digital spaces. Using a normative juridical approach, the study reviews statutory regulations, legal principles, and relevant case decisions. The findings indicate that although Articles 27 and 28 of the ITE Law offer a comprehensive legal framework for addressing false news, several issues remain, including overlapping norms, ambiguous terminology, and challenges in law enforcement practices. These limitations affect the consistency of sanctions and the proportionality of criminal liability. The study concludes that clearer guidelines, improved legal interpretation, and strengthened digital literacy are essential to enhance the effectiveness of sanctions and ensure the fair application of the law.